2007
DOI: 10.1038/sj.clpt.6100069
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Extrapyramidal Syndrome in Schizophrenic Patients Treated with Antipsychotics: A Population-based Study

Abstract: To compare the prevalence of extrapyramidal syndrome (EPS) between the first-generation antipsychotics (FGAs) and second-generation antipsychotics (SGAs), the co-prescribing rate of anti-Parkinson drugs (APDs) of each antipsychotic drug was analyzed using population database. Fourteen antipsychotics had been prescribed during the 5-year study period. Among the SGAs, quetiapine had the lowest crude co-prescribing rate of APDs (27.09%), whereas risperidone had the highest rate (66.50%). Among the FGAs, thioridaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 56 publications
3
29
0
Order By: Relevance
“…However, it would be of great value to evaluate the Slack channel-modulating properties of loxapine and amoxapine hydroxylated derivatives. With respect to side effects, loxapine is known to be among the tricyclic antipsychotic agents most prone to inducing extrapyramidal syndrome (EPS), as shown by the very high rate of antiparkinsonism drug coprescription associated with loxapine use (Yang et al, 2007). Moreover, the study conducted by Yang et al (2007) confirmed previously published studies, supporting a quantitative correlation between the dosage administered and the EPS incidence rate (Ereshefsky, 1999).…”
Section: Downloaded Fromsupporting
confidence: 78%
“…However, it would be of great value to evaluate the Slack channel-modulating properties of loxapine and amoxapine hydroxylated derivatives. With respect to side effects, loxapine is known to be among the tricyclic antipsychotic agents most prone to inducing extrapyramidal syndrome (EPS), as shown by the very high rate of antiparkinsonism drug coprescription associated with loxapine use (Yang et al, 2007). Moreover, the study conducted by Yang et al (2007) confirmed previously published studies, supporting a quantitative correlation between the dosage administered and the EPS incidence rate (Ereshefsky, 1999).…”
Section: Downloaded Fromsupporting
confidence: 78%
“…Olanzapine was administered as monotherapy in most studies of schizophrenia, except in a small number of prospective observational or retrospective studies 2831. In these studies, combinations with other antipsychotics were specifically allowed or reflected the naturalistic setting of the study design.…”
Section: Resultsmentioning
confidence: 99%
“…30,31,35,37,66,69–79 Two studies also investigated the risk of pneumonia associated with second-generation antipsychotics, including olanzapine (Table 6). 28,33…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, it tests the propensity to initiate a marker drug (e.g., trihexyphenidyl) after use of an index drug (e.g., antipsychotics), where the index drug is suspected inducing a side effect (e.g., extrapyramidal symptom) that warrants treatment with the marker drug [22]. Theoretically, if there is no causal relationship between index and marker drugs, it is equally possible for patients to initiate the marker drug before or after index drug initiation; resulting in a symmetrical (or random) prescribing pattern of the marker drug around index drug initiation.…”
Section: Methodsmentioning
confidence: 99%